Preliminary report on osteochondrosis in cattle in the north-western parts of South Africa - Leon Prozesky (Onderstepoort Journal of Veterinary Research, 2016)
The north-western part of South Africa, in particular, is well known for mineral imbalances. Aphosphorosis, resulting in rickets and osteomalacia, received a lot of attention at the turn of the nineteenth century (1882–1912). This was followed in 1997 by research on Vryburg hepatosis, another area-specific mineral imbalance–related disease in young calves reared on manganese-rich soil derived from the weathering of dolomitic (carbonate) rock formations. In 1982, a totally new syndrome (osteochondrosis) manifested in, amongst others, areas in South Africa where aphosphorosis was rife. Osteochondrosis was also identified in the south-western parts of Namibia as well as southern Botswana and other areas in South Africa. Osteochondrosis has a multifactorial aetiology and this study focused on the role of minerals, particularly phosphorus, in the development of the disease. A significant improvement in the clinical signs in experimental animals and a reduction of osteochondrosis occurred on farms where animals received bioavailable trace minerals and phosphorus as part of a balanced lick. An increase in the occurrence of the disease on farms during severe drought conditions in 2012–2013 prompted researchers to investigate the possible role of chronic metabolic acidosis in the pathogenesis of the disease.